2016
DOI: 10.1007/s10903-015-0326-6
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into Suicides Among Bhutanese Refugees Resettled in the United States Between 2008 and 2011

Abstract: An increase of Bhutanese refugee suicides were reported in the US between 2009 and 2012. This investigation examined these reported suicides in depth to gain a better understanding of factors associated with suicide within this population. The study employed 14 psychological autopsies to elicit underlying motivations and circumstances for self-inflicted death and to identify potential future avenues for prevention and intervention among refugee communities. Disappointment with current (un)employment, lack of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 42 publications
2
52
0
1
Order By: Relevance
“…The structured closed ended section followed the themes outlined in the original PA method (21) as well as more recent approaches (22, 23). The lead author has used this method in a US-based ethnically Nepali Bhutanese refugee population experiencing high suicide rates (24). To assess histories of depression, we used the Nepali Patient Health Questionnaire (PHQ-9), a widely-used instrument around the world that has been locally validated and proven to perform well in our target population: locally validated cutoff ≥ 10: sensitivity=0.94, specificity=0.80 (25).…”
Section: Methodsmentioning
confidence: 99%
“…The structured closed ended section followed the themes outlined in the original PA method (21) as well as more recent approaches (22, 23). The lead author has used this method in a US-based ethnically Nepali Bhutanese refugee population experiencing high suicide rates (24). To assess histories of depression, we used the Nepali Patient Health Questionnaire (PHQ-9), a widely-used instrument around the world that has been locally validated and proven to perform well in our target population: locally validated cutoff ≥ 10: sensitivity=0.94, specificity=0.80 (25).…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have investigated the reasons for the higher rate of suicidal ideation among refugees versus the host population. 5 6 7 8 9 First, there is a perspective that the high rate of suicidal ideation among refugees originates from post-traumatic stress disorder (PTSD) or depression related to negative experiences associated with exile and resettlement. 6 7 8 9 In contrast, other study has suggested that PTSD and depression had no association with suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…Over 94,000 Bhutanese refugees have resettled in the United States since 2008, the start of Bhutanese resettlement in the country 1 . Although resettlement has led to increased safety, scholastic and vocational opportunities, and improved living conditions and a better quality of life for many Bhutanese refugees, many also struggle with resettlement stressors, including acculturation difficulties, financial insecurity, housing instability, and separation from family 2 . Many caregivers have had to learn to navigate the American school system and respond to their children's academic difficulties without having received any formal education themselves.…”
Section: The Bhutanese Refugee Experiencementioning
confidence: 99%
“…Furthermore, stressors in resettlement such as language and cultural barriers, unemployment, lack of social support, economic instability have been associated with mental health problems, including depression and anxiety 25 . Indeed, when families face postmigration difficulties, their sense of hope and future can diminish, increasing risk for mental illness 2,24 . For refugee youth and families who often view school as the most important factor contributing to future success, education can play a prominent role in preserving hope 26,27…”
Section: The Bhutanese Refugee Experiencementioning
confidence: 99%